APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK PENENTUAN LOKASI TEMPAT PEMBUANGAN AKHIR (TPA) BARU SAMPAH DAN RUTE ANGKUTAN SAMPAH DI KOTA TANGERANG SELATAN - Farhan Naufal Azmi, - (2022)
South Tangerang City is a large waste producer, namely the production of waste in South Tangerang is currently almost 900 tons per day with a population of 1.6 million people. The existence of the Final Disposal Site (TPA) in South Tangerang City is also not capable of storing such abundant waste and there is only one TPA, namely TPA Cipeucang which is located in Serpong District. As one solution, it is very important to determine the location of the new TPA, which is based on the Indonesian National Standard on determining the location of the TPA. The main objective of this research is to map suitable areas for landfill in South Tangerang City based on SNI and determine the exact location. This study also analyzes the suitability of the existing landfill and determines the route to the selected area as a new landfill. The method used is Geographic Information Systems and network analysis to determine the route of waste transportation. South Tangerang City has a very inappropriate class classification to a very appropriate class. The appropriate Samgat class is in 2 locations, namely Kranggan, Setu and Jelupang Districts, North Serpong District, while the most suitable location is in Kranggan, Setu District because it has a higher score of 60 from the maximum total score of 67. Cipeucang landfill The existing ones are included in the Incompatible classification, with a score of 38 out of a maximum score of 67. The route from the TPS to the selected TPA in Kranggan has an average mileage of 10.80 km which is still included in the standard mileage from TPS to TPA, which is under 20 km. Keywords: TPA, Waste, Route